Hybrid carbon fiber-carbon nanotubes reinforced polymer composites: A review - Zakaria, M.R. (Elsevier Ltd, 2019)
As a result of its impressive 3D network structure form, a great deal of interest has thus been generated among the science community on the hybridization of carbon fiber (CF) and carbon nanotube (CNT). Although there had been a large amount of studies conducted on this novel hybrid material, there are however, limited reviews being published on their fabrication methods and performances in polymer composites. For this reason, apart from collectively introducing and discussing the advantages and limitations of the hybrid CF-CNT based on various fabrication methods such as those of chemical vapour deposition, electrophoretic deposition, electrospray deposition and chemical functionalization, this study had also examined and compared the detailed performances of each of the hybrid CF-CNT reinforced polymer composite based on their fabrication methods through its mechanical, electrical and thermal properties. Â© 2019 Elsevier Ltd